STUDY ON ETYMOLOGY METHOD ON STUDENT’S READING SKILL - Arief Wahyudi (Penerbit STKIP PGRI Bangkalan, 2022)
Reading’s ability as a method of learning English is one of the most effective ways to improve vocabulary. According to Samra that Students’ reading ability is also often an important point when learning English. The laziness to read students mostly arises from each individual. So that the level of understanding of students will decrease. Besides the importance of the existence of facilities such as computers, laptops, cellphones, and internet support using reverse class learning. Reverse learning classes give students the opportunity to be able to study material by looking for reading texts on the internet as a provision for prior knowledge class session learning. The teacher must understand every development of the technological age as it is today. This study aims to describe the implementation and the students’ responses toward etymology method in teaching reading. The research design of the study was qualitative which focus on case study research. It involved the Eleventh Grade ofStudents at MA An-Nidomiyah as the subject of the research. The data were obtained through the observation during the teaching and learning process and an interview with the students. In this study, the researcher accomplished several steps to analyze the data, namely organizing and familiarizing, coding and reducing, interpreting and representing. The result of the research finding prove that it iseffective to use this method. So, using etymology method can improve reading skills and knowledge of vocabularyies. Furthermore, it is suggested that etymology methodcan be effectively used in reading class.